Rural and Urban Differences in Nebraskans' Access to Marijuana, Methamphetamine, Heroin, and Prescription Pills. (October 2018) - Habecker, Patrick; Welch-Lazoritz, Melissa; Dombrowski, Kirk
The ability of a user to access a given type of drug is related to the configuration of the market for that drug, and a range of economic and criminal justice concerns. This study focuses on Nebraskan's "ready access" to four types of drugs (marijuana, methamphetamine, heroin, and prescription pills) in 2016, using a statewide survey of housed Nebraskan adults. Ready access is defined as a participant knowing at least one person from whom they could obtain a given type of drug if they wanted to. We found that 35% of adult Nebraskans knew at least one person from whom they could obtain marijuana, 8.9% for methamphetamine, 4.5% for heroin, and 17.8% knew at least one source for prescription pills. Relationships between knowing a source for each type of drug and rurality, sex, race, religious attendance, mental health symptoms, and education are explored.